Alkohol in zdravila - Peterlin-Mašič, Lucija (Farmacevtski vestnik, 2018)
Ethanol is one of the most widely used legal psychoactive substances with high potential for abuse. Interactions between ethanol and drugs may occur with the concurrent use of ethanol and medicinal products. Elderly frequently use ethanol and prescription drugs concurrently, therefore the risk for side effects is higher. Concomitant use of ethanol and drugs may result in pharmacokinetic or pharmacodynamic interactions. Pharmacokinetic interactions occur, when ethanol directly affects the normal metabolism of the drug and its concentration in the blood. Pharmacodynamic interactions are primarily the result of additive effects of ethanol and drugs on the central nervous system. Therefore, there is a risk of excessive sedation when using drugs that act depressive on the central nervous system. In reality, interactions between ethanol and drugs are often complex, as people maybe exposed to more than two psychotropic substances at the same time. In this review, we focused primarily on action of the ethanol on organism and on providing a better insight into the mechanisms underlying the known pharmacokinetic and pharmacodynamic drug interactions with ethanol.
Keywords: Alkohol; drug; etanol; ethanol; interakcije učinkovin; kombinacije učinkovin; Zdravila